2021
DOI: 10.20473/spmrj.v3i2.20976
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hamstrings and Quadriceps Femoris Muscle Thickness Increment between Agonist-Antagonist Paired Set and Traditional Set Resistance Training in Untrained Healthy Subjects

Abstract: Background: Resistance training is an effective way to increase muscle mass. Resistance training with agonist-antagonist paired set method can be an alternative to increase muscle mass within a relatively short training time.Aim: To compare the increase in hamstrings and quadriceps femoris muscle thickness between agonist-antagonist paired set (APS) and traditional set (TS) resistance training in untrained healthy subjects.Material and Methods: This study was an experimental study on 16 untrained healthy men w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…It can be analyzed that curcumin-activated myogenesis in the form of stimulation of muscle cell proliferation is not sufficient to increase the diameter of muscle fibers. However, the immunohistochemistry analysis was not performed in this study that might explain the beneficial effect of oral curcumin in skeletal muscle metabolism.Furthermore, resistance exercise alone can increase muscle mass in human by stimulating intracellular anabolic signals.These intracellular anabolic signals further increase protein synthesis and reduce protein degradation 21. Both intervention groups in this study that performed resistance exercise, with or without oral curcumin, showed significant difference in increased muscle fiber diameter compared to control group.…”
mentioning
confidence: 60%
“…It can be analyzed that curcumin-activated myogenesis in the form of stimulation of muscle cell proliferation is not sufficient to increase the diameter of muscle fibers. However, the immunohistochemistry analysis was not performed in this study that might explain the beneficial effect of oral curcumin in skeletal muscle metabolism.Furthermore, resistance exercise alone can increase muscle mass in human by stimulating intracellular anabolic signals.These intracellular anabolic signals further increase protein synthesis and reduce protein degradation 21. Both intervention groups in this study that performed resistance exercise, with or without oral curcumin, showed significant difference in increased muscle fiber diameter compared to control group.…”
mentioning
confidence: 60%